Sedimentology and depositional environment of a marine target, Southern Namibia: 3D stratigraphic architecture and diamond mineralisation potential - Runds, Megan Jean (Department of Geological Sciences, 2018)
The world's largest diamond placer lies on the southwestern coast of Namibia, within the restricted area known as the Sperrgebiet, and comprises, amongst others, a series of Plio-Pleistocene to Holocene littoral deposits preserved onshore for >120 km northwards from the Orange River mouth. Through comprehensive seismic and sedimentological analysis, this study provides the first attempt at linking the well-documented onshore diamondiferous deposits of the Sperrgebiet with the submerged landscape of a diamondiferous marine target, called the Purple Target Area (PTA), situated beneath up to 70 m of seawater, some 3.5 km offshore of the onshore deposits. Four seismic units (A - D) have been identified on 2D seismic reflection profiles, and calibrated to lithological data from several boreholes. These have then been integrated into a detailed landscape evolution model for the PTA. The principal controls on the stratigraphic development of the PTA are rate of sediment input and relative sea-level (RSL) fluctuations. The latter is defined as the interplay of vertical tectonic changes in accommodation space and eustatic sea-level (ESL) fluctuations. The most noteworthy phase of deposition within the PTA basin is the normal regressive coarse gravel beaches trending shore parallel, with the primary gravel barrier and its preserved coeval back-barrier deposits exceeding 7 km in length. The approximate age of the PTA gravel beaches, due to a lack of absolute age constrains, are estimated with reference to their correlated water depths (palaeo-bathymetry) in relation to the ESL curve. Based on this approximation, the PTA gravel beaches have survived the transgression and erosive wave-ravinement processes associated with the Late Pleistocene-Holocene, which occurred between 19 and 7 ka before present. The preservation of the primary gravel barrier beach complex is linked here to a rapid RSL rise during the last transgression, namely Meltwater Pulse 1B. The smaller gravel beaches that are landward of the main barrier were partially preserved through overstepping, but endured more intense ravinement associated with the rapid RSL rise. The primary gravel barrier complex preserved the same cross-beach variability in clast shape sorting (disc/blades and spherical clasts consistent with the middle section and seaward section of the gravel beach, respectively) and back-barrier lagoonal facies identified laterally across the locally known ED barrier beach complex, preserved onshore 65 km south of the PTA. The sedimentary facies correspondence between the onshore and offshore deposits presents a rare opportunity to study the emplacement and preservation processes of gravel beach deposits on a high energy shelf. In addition, the diamond mineralisation potential of the offshore gravel beaches can be assessed with respect to the well-documented onshore diamondiferous beaches.